Dairi storytelling and stories in the Batak Reader of Herman Neubronner van der Tuuk - Papenhuyzen, Clara Brakel (UI Scholars Hub, 2016)
In this article I first discuss how texts of Dairi stories collected in the nineteenth century by Herman Neubronner van der Tuuk relate to storytelling, and question whether the development of written versions of stories necessarily endangers the practice of storytelling. Then I investigate how written versions of Dairi stories in Van der Tuuk's Batak Reader relate to each other and to the printed text, based on texts in manuscripts collected by Van der Tuuk. In conclusion I discuss the possible aim of Van der Tuuk's Batak Reader, focussing on the Dairi section, which has not been dealt with in earlier publications.